The World Cultural Heritage in Beijing. (The World Cultural Heritage in Beijing.)
v.1-The Great Wall ; v.2-The ming Tombs ; v.3-The Palace Museum ; v.4-Peking Man site of Zhoukoudian ; v.5-The Summer Palace ; v.6-The Temple of Heaven.